(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The proposal of this research was the structural analysis of a chassis for a Formula SAE by means of finite element software with the objective of analyzing the structural behavior with different materials according to the standards stipulated by the technical regulations. For this, a quantitative approach was used in which the difference between the data of design one and the other designs was evaluated, and the mechanical characteristics of the materials were determined by means of the research method. Finally, the best performing design was defined using the statistical method in which the results of the structural analysis obtained in the finite element software were presented. The results of the analysis showed that the optimum material for the structure was A500 Steel with a weight of 51.2 kg, a deformation of 0.16 mm was achieved in the belt test and a tension of 38.59 MPa. The values obtained in the simulations are compared with design 1 in its legal basis. From the simulations performed, it is determined that design 3 complies with the requirements stipulated by the Formula SAE regulations using materials at world, regional and national level; determining that the A500 steel considered as national material presents better performance for this type of competition.